2016
DOI: 10.1371/journal.pgen.1005884
|View full text |Cite
|
Sign up to set email alerts
|

A RUNX2-Mediated Epigenetic Regulation of the Survival of p53 Defective Cancer Cells

Abstract: The inactivation of p53 creates a major challenge for inducing apoptosis in cancer cells. An attractive strategy is to identify and subsequently target the survival signals in p53 defective cancer cells. Here we uncover a RUNX2-mediated survival signal in p53 defective cancer cells. The inhibition of this signal induces apoptosis in cancer cells but not non-transformed cells. Using the CRISPR technology, we demonstrate that p53 loss enhances the apoptosis caused by RUNX2 knockdown. Mechanistically, RUNX2 provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 39 publications
(57 reference statements)
1
47
0
Order By: Relevance
“…Interestingly, the p53 cellular protein acts as a negative regulator of osteoblastogenesis under normal conditions, repressing transcription factor such as Osterix and Runx2 (11), which are required in the initial osteogenesis phase in osteoprogenitor cells (12,13). However, Runx2 may act by inhibiting the function of p53 in activating apoptosis by inducing c-MYC transcription by histone modifications (14). This explains the highly elevated Runx2 expression levels in OS cells.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the p53 cellular protein acts as a negative regulator of osteoblastogenesis under normal conditions, repressing transcription factor such as Osterix and Runx2 (11), which are required in the initial osteogenesis phase in osteoprogenitor cells (12,13). However, Runx2 may act by inhibiting the function of p53 in activating apoptosis by inducing c-MYC transcription by histone modifications (14). This explains the highly elevated Runx2 expression levels in OS cells.…”
Section: Introductionmentioning
confidence: 99%
“…This growth inhibition was associated with reduced interactions between CBFβ and RUNX1, reduced RUNX1 occupancy on target genes and altered gene expression . Furthermore, Shin et al recently demonstrated that knockdown of RUNX2 or CBFβ induces apoptosis in some human OS cell lines, and identified potential downstream effectors responsible for this activity, including MYC . Another recent study identified tumour suppressive activity of a microRNA through its targeting of RUNX2 in OS cells .…”
Section: Discussionmentioning
confidence: 97%
“…37 Furthermore, Shin et al recently demonstrated that knockdown of RUNX2 or CBFβ induces apoptosis in some human OS cell lines, and identified potential downstream effectors responsible for this activity, including MYC. 38 Another recent study identified tumour suppressive activity of a microRNA through its targeting of RUNX2 in OS cells. 39 Thus, in this study, we aimed to identify whether inhibiting the interaction between RUNX2 and CBFβ, using allosteric inhibitors of CBFβ, would be sufficient to induce antitumour effects in canine OSA cell lines or if this activity may require knockdown of RUNX2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…For ChIP-seq, we followed our previous procedures without major modifications (He et al., 2015, Li et al., 2012, Shin et al., 2016). Pathway analyses using DAVID Bioinformatics Resources were previously described (Huang da et al., 2009, Lee et al., 2010).…”
Section: Methodsmentioning
confidence: 99%